Emergence of epidemic Neisseria meningitidis serogroup C in Niger, 2015: an analysis of national surveillance data. Issue 11 (November 2016) - Sidikou, Fati; Zaneidou, Maman; Alkassoum, Ibrahim; Schwartz, Stephanie; Issaka, Bassira; Obama, Ricardo; Lingani, Clement; Tate, Ashley; Ake, Flavien; Sakande, Souleymane; Ousmane, Sani; Zanguina, Jibir; et al.
Summary: Background: To combat Neisseria meningitidis serogroup A epidemics in the meningitis belt of sub-Saharan Africa, a meningococcal serogroup A conjugate vaccine (MACV) has been progressively rolled out since 2010. We report the first meningitis epidemic in Niger since the nationwide introduction of MACV. Methods: We compiled and analysed nationwide case-based meningitis surveillance data in Niger. Cases were confirmed by culture or direct real-time PCR, or both, of cerebrospinal fluid specimens, and whole-genome sequencing was used to characterise isolates. Information on vaccination campaigns was collected by the Niger Ministry of Health and WHO. Findings: From Jan 1 to June 30, 2015, 9367 suspected meningitis cases and 549 deaths were reported in Niger. Among 4301 cerebrospinal fluid specimens tested, 1603 (37·3%) were positive for a bacterial pathogen, including 1147 (71·5%) that were positive for N meningitidis serogroup C (NmC). Whole-genome sequencing of 77 NmC isolates revealed the strain to be ST-10217. Although vaccination campaigns were limited in scope because of a global vaccine shortage, 1·4 million people were vaccinated from March to June, 2015. Interpretation: This epidemic represents the largest global NmC outbreak so far and shows the continued threat of N meningitidis in sub-Saharan Africa. The risk of further regional expansion of this novel clone highlights the need for continued strengthening of case-based surveillance. The availability of an affordable, multivalent conjugate vaccine may be important in future epidemic response. Funding: MenAfriNet consortium, a partnership between the US Centers for Disease Control and Prevention, WHO, and Agence de Médecine Preventive, through a grant from the Bill & Melinda Gates Foundation.